Faktor-Faktor yang Mempengaruhi Tingkat Produksi Kelapa Sawit (Elaeis guineensis Jacq.) Di Desa Laburan Kecamatan Paser Belengkong Kabupaten Paser - Fikri Jufri; Junaidi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2020)
The purpose of this study was to determine: (i) the effect of factors of production, namely the number of trees, labor and fertilizer costs simultaneously on the level of oil palm production in Laburan Village, (ii) the influence of production factors such as the number of trees, labor and fertilizer costs partially to the level of oil palm production in Laburan Village, (iii) how much the contribution of production factors such as the number of trees, labor, and fertilizer costs to the creation of oil palm in Laburan Village, (iv) what factors most dominant influence oil palm production in Laburan Village. This research uses descriptive statistical analysis methods. Research carried out in Laburan Village, Paser Belengkong District, Paser Regency in June - October 2018, with a population of oil palm plantations totaling 154 farmers. The method of taking a sample of purposive sampling and obtained a sample of 23 respondents. The results of this study indicate that the factors of production simultaneously affect the level of production, of the three elements of production the number of trees and fertilizer costs partially significantly affect the level of output while the factors of labor production somewhat do not significantly affect the level of the production, production factors have a positive contribution to the level of the output, and the number of trees is the most dominant factors affecting the level of oil palm production in Laburan Village, Paser Belengkong District, Paser Regency